Efeito da respiração espontânea e ventilação mecânica Invasiva na frequência de força tetânica e parâmetros Indicativos da disfunção diafragmática em modelo animal: revisão sistemática com meta-análise - Caetano, Heliard Rodrigues dos Santos (2022)
Introduction: Lung diseases and severe brain injuries may require the use of spontaneous breathing (SB) or invasive mechanical ventilation (IMV). The invasive form can lead to several complications, mainly respiratory muscle failure, due to decreased inspiratory muscle strength and resistance and diaphragmatic muscle atrophy. Objective: The objective was to investigate validated parameters on the effects of the SB intervention, compared with the VMI control, in rats as an animal model. Methodology: Searches were carried out in the following databases: “PubMed”, “ScienceDirect”, “Web of Science”, “Virtual Health Library - BVS”, and Google in March 2021 and repeated in March 2022. keywords “Respiration, artificial”; “rats”; "mice". 12 eligible articles were included in the meta-analyses. Results: The results demonstrate a significant difference (p<0.05) of the intervention associated with the diaphragmatic muscle in parameters: frequency of diaphragmatic force (N/cm2); cross-sectional area (µm2) of diaphragmatic fibers (I, IIa and IIx/b); contraction force (N/cm2) and tetanic force (N/cm2) the results revealed a significant difference (p<0.05) in the tetanic force parameter (N/cm2). Conclusion: It is concluded that SB attenuates the loss of diaphragmatic force frequency; cross-sectional area of fibers (I, IIa and IIx/b), contraction force and diaphragmatic tetanic force in male rats, as an experimental model.